Regionalismo y movilización ciudadana. La huelga de pagos de Cartago de 1962 - Alvarenga Venutolo, Patricia (Revista de historia., 2002)
The mobilization of Carthage as well as others of regional character of the time, proposed rather to put a limit to the expansive process of the State. The mobilizations related to the water service, among which those organized by the left stand out, were radically opposed to the process of expansion of Aqueducts and Sewers, pronouncing themselves in favor of this service remaining in the hands of the municipalities, which, however, did not get rid of becoming centers of tension due to the price and quality of the service.